Preparation and characterization of PLA filaments for FDM 3D printing / Amir Yusuf Mohd Shukri ... [et al.] - Mohd Shukri, Amir Yusuf; Abdullah, Abdul Manaf; Shuib, Solehuddin; Mohamad, Dasmawati (UiTM Press, 2025)
Polylactic acid (PLA) is the predominant filament material utilised in fused deposition modelling (FDM) 3D printing. Despite being commonly utilised in FDM 3D printing, the fabrication of PLA filament involves a complex extrusion process that is not widely reported. This study aims to assess the thermal and melt flow behaviour of PLA. Besides, the impact of pulling speed on the resulting filament in terms of diameter, morphologies as well as mechanical properties was also quantified. The thermal behaviour of the PLA was evaluated using a thermogravimetric analyser and differential scanning calorimetry. Meanwhile, the flow rate of PLA was assessed using a melt flow indexer. The PLA was processed into a filament form using a single-screw extruder at three different pulling speeds of 500 rpm, 650 rpm, and 800 rpm, followed by an evaluation of its mechanical properties using a universal testing machine. The thermal properties data showed that the PLA started decomposing at 341 °C and melted at 170.9 °C. The melt flow rate of the PLA was 17 g/10 mins. The pulling speed of 500 rpm produced an optimal filament with a mean diameter of 1.785 mm. However, the strength and strain of the respected filament were slightly lower than those fabricated at pulling speeds of 650 rpm and 800 rpm. The ideal PLA filament was successfully fabricated at a pulling speed of 500 rpm. The findings from this study could be a stepping stone toward the fabrication of an enhanced PLA-based filament to be used for various applications.